Weed Control in Tomato - William M. Stall; James P. Gilreath (EDIS)
Revised! HS-200, a 5-page fact sheet by William M. Stall and James P. Gilreath, describes effective weed management practices for tomato in Florida and provides a table listing herbicides available to growers for chemical weed control. This publication updates the 2003 table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.